Feasibility verification and bending property of web-reinforced foam sandwich composites prepared via thermal expansion molding process. (15th August 2022) - Min, Wei; Tao, Lei; Yan, Zhi; Peng, Suping; Qi, Liangliang; Yu, Xuduo; Wan, Yujia; Chen, Haiping; Yu, Muhuo; Sun, Zeyu
Abstract: Web-reinforced foam sandwich structures have excellent mechanical properties due to the enhancement of the structural moment of inertia and the increase in the degree of integration. The present study prepared foam sandwich composites and web-reinforced foam sandwich composites through a novel thermal expansion molding process (TEMP). In addition, four conventional structures, including laminate, foam sandwich, I-beam composite, and web-reinforced foam sandwich structures, were prepared using vacuum-bag-only (VBO) technology. The feasibility of the technology was explored through the structure and properties of foam, the matching of foam and resin, and the porosity of the composites after forming. The three-point bending test showed that the stiffness and strength of the web reinforced foam sandwich prepared by TEMP technology are increased by 18.8% and 4.1%, respectively, compared with VBO technology. Moreover, the TEMP technology was more effective in processing the sandwich composite compared with the VBO technology. The failure mechanisms of the web-reinforced foam sandwich composite for the three-point bending experiment were determined by finite element analysis (FEA), and the accuracy of the finite element model was verified. The TEMP technology involved in this research provides guidance for the application of complex web-reinforced foam sandwich composites in the field of lightweight.